Culture-Based and Culture-Independent Assessments of Endophytic Fungal Diversity in Aquatic Plants in Southwest China - Zheng, Hua; Qiao, Min; Xu, Jianping; Yu, Zefen (Frontiers in Fungal Biology, 2021)
Aquatic ecosystems contain tremendous plant and microbial diversity. However, little is known about endophyte diversity in aquatic plants. In this study, we investigated the endophytic fungal diversity in aquatic plants in southwest China using both culture-based and culture-independent high-throughput sequencing methods. A total of 1697 fungal isolates belonging to four phyla and 158 genera were obtained from 15,373 plant tissue segments of thirty aquatic plant species. The overall most abundant endophytic fungi were those in Ascomycete genera Penicillium, Aspergillus, Fusarium, Phoma, Ceratophoma and Plectosporium. No difference in fungal isolation rates was observed among tissues from roots, stems, and leaves. Twenty tissue samples from three most common plant species were further subjected to culture-independent meta-barcode sequencing. The sequence-based analyses revealed a total of 1074 OTUs belonging to six fungal phyla and 194 genera. Among the three plants, Batrachium bungei harbored the highest number of OTUs. Besides, a total of 66 genera were detected by two methods. Both the culture-dependent and independent methods revealed that aquatic plants in southwest China have abundant endophytic fungal diversity. This study significantly expands our knowledge of the fungal community of aquatic plants.